Diary of a wimpy kid : double down - Kinney, Jeff (New York : Amulet Books, an imprint of ABRAMS, 2016)
Greg's mom thinks video games are turning his brain to mush, so she wants her son to put down the controller and explore his creative side. When Greg discovers a bag of gummy worms, it sparks an idea. Can he get his mom off his back by making a movie . . . and will he become rich and famous in the process? Or will doubling down on this plan just double Greg's troubles?
Keywords: Halloween -- Juvenile fiction; Video games -- Juvenile fiction; Families -- Juvenile fiction; Diaries -- Juvenile fiction